Assessment of patients presenting in shock at emergency department in a tertiary care teaching hospital - Bajracharya, Sumana; Shrestha, Ashis; Shrestha, Roshana; Thapa, Rashmi; Acharya, Samita; Hada, Kabita (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Clinical profile of patient presenting with shock is important in early recognition and intervention to improve outcome especially in resource limited setup. This study is designed with an objective to evaluate history, clinical findings, laboratory findings and provisional diagnosis of patient presenting with shock.Methods: This was a cross sectional observational study conducted at Patan Hospital emergency department from September to November 2014. All consecutive patients presenting with shock were included. Patient’s demography (age, sex), provisional diagnosis, major findings (blood pressure, lactate, total count, fluid given, stay in emergency), requirement of inotropes and improvement were analyzed.Results: In three months period, 38 patients presented with shock to the emergency. Out of them 21 (55.3 %) were female and 17 (44.7%) were male. Commonest presenting complain was fever and shortness of breath 12 (31.6%), diarrhea 6 (13.4%) and shortness of breath 5 (13.2%). Septic shock was seen in 17 (44.7%), hypovolemic in 10 (26.3%), cardiogenic 7 (18.4%) and unclassified 4 (10.5%). Mean duration of stay in emergency was 100.6 minutes. Mean fluid given in emergency was 2328.9 milliliters.Conclusions: Sepsis was an important cause of shock in the emergency department. Pneumonia was common cause of sepsis and chronic obstructive pulmonary disease was common underlying condition.Journal of Patan Academy of Health Sciences, Vol. 3, No. 1, 2016, Page: 18-22